A method for determining the resin content and fiber surface density of prepreg
By using a mixed solvent of dichloromethane and N-methylpyrrolidone for ultrasonic cleaning, the problems of large reagent usage and low treatment efficiency in the existing prepreg measurement methods were solved, and efficient and accurate measurement of resin content and fiber surface density content were achieved.
Patent Information
- Application Number
- CN202510090894.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-04
AI Technical Summary
In the existing prepreg measurement methods, the reagent is used in large amounts, low treatment efficiency, and the number of cleanings is often caused by fiber damage or loss, which affects the accuracy of the measurement results.
Ultrasonic cleaning is performed using a mixed solvent of dichloromethane and N-methylpyrrolidone. The effective decomposition of resin and fiber can be achieved through 4 ultrasonic treatments, reducing bonding phenomena and white precipitates, improving cleaning efficiency and measurement accuracy.
It significantly reduces the amount of solvent and the number of cleaning times, improves the working efficiency and stability and accuracy of the measurement results, and is suitable for the treatment of epoxy prepregs or polyester prepregs with resin content of 33-50%.
Smart Images

Figure CN119757109A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of prepreg determination, in particular to a method for determining the resin content and fiber surface density content of prepreg. Background Art
[0002] Prepreg refers to a composite material product that is pre-mixed with a resin matrix and a reinforcing material and processed by a specific process. It has a specified thickness and width and can be further processed and formed. Prepreg can be divided into two categories: thermoplastic prepreg and thermosetting prepreg according to the different resin matrices. Thermoplastic prepreg can be melted and plasticized when heated, while thermosetting prepreg will undergo chemical cross-linking and curing when heated.
[0003] In the existing method, according to the difference of prepreg types, different solvents are used to separate the reinforcement and matrix at different temperatures, and the content of the resin and the proportion of the fiber surface density are tested. Wherein, when the prepreg is soaked with a solvent, the solvent is kept in full contact with the sample to dissolve the resin matrix completely, without changing the quality of the reinforcing material and the filler, and a glass rod is used to stir or an ultrasonic wave is used to accelerate the separation of the resin and the fiber. However, when the prepreg is soaked with a solvent at present, a single solvent (such as acetone, ethanol, dichloroethane, dichloromethane, dimethylformamide) is often used and the amount is large, and a single sample uses at least 2100mL of reagent, and some of the solvents used are controlled products, such as acetone, etc.; the processing efficiency is low, and it is generally necessary to repeat 7-8 times of cleaning to be clean, and it is necessary to soak ultrasound + glass rod stirring treatment at the same time, so that the resin and fiber of the sample can be decomposed; in addition, more cleaning times, it is easy to cause damage or loss of the fiber, and white precipitates will appear in the process, and the fiber will have a more serious bonding phenomenon after stirring, which affects the result judgment.
[0004] Therefore, further research is needed on the determination method of prepreg when determining the resin content and fiber surface density content. Summary of the invention
[0005] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is how to reduce the amount of reagents used and simplify the pretreatment process for the prepreg to be tested, while improving the cleaning efficiency and the stability and accuracy of determining the resin content and fiber surface density. To this end, the present invention provides a method for determining the resin content and fiber surface density of a prepreg.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] The present invention provides a method for determining the resin content and fiber surface density content of a prepreg, comprising the following steps:
[0008] (1) Cool the dried container to room temperature and keep it constant, then weigh the container;
[0009] (2) cutting the prepreg sample to be tested, placing it into the container of step (1), and weighing the total weight of the container and the prepreg sample to be tested;
[0010] (3) adding a mixed solvent to the container of step (2), pouring out the mixed solvent after the first ultrasonic treatment; continuing to add a new mixed solvent, pouring out the mixed solvent after the second ultrasonic treatment, and then adding a new mixed solvent, repeating the ultrasonic treatment for a total of 4 times; after the ultrasonic treatment, the remaining fiber in the container is the treated fiber; the mixed solvent is dichloromethane and N-methylpyrrolidone;
[0011] (4) drying the fiber together with the container, cooling to room temperature and constant weight after drying, and weighing the total weight of the container and the fiber;
[0012] (5) Calculate the resin content and fiber surface density of the prepreg sample to be tested respectively.
[0013] Preferably, in step (1), the drying temperature is 120°C ± 2°C and the drying time is 60 min.
[0014] Preferably, in step (2), the prepreg sample to be tested is epoxy prepreg or polyester prepreg; the resin mass content of the prepreg sample to be tested is 33-50%;
[0015] Preferably, in step (2), a sample ≥50 mm away from the edge is selected as the prepreg sample to be tested, the area of the prepreg sample to be tested is recorded as A, and the size of the selected prepreg sample to be tested is (100±1) mm×(100±1) mm.
[0016] Preferably, in step (2), after shearing, the size of the prepreg sample to be tested is ≤10 mm×100 mm.
[0017] Preferably, in step (3), the ratio of the mass of the prepreg sample to be tested to the volume of the mixed solvent added once is (4-6) g:100 mL.
[0018] Preferably, in step (3), the volume ratio of methylene chloride and N-methyl pyrrolidone in the mixed solvent is (8-2): (2-8). Methylene chloride and N-methyl pyrrolidone are mixed according to this ratio range, and four ultrasonic treatments are performed as the processing solvent of epoxy prepreg or polyester prepreg, which can not only efficiently dissolve the resin matrix in epoxy prepreg or polyester prepreg, but also will not destroy the reinforcement of epoxy prepreg or polyester prepreg, so that epoxy prepreg or polyester prepreg will neither have bonding phenomenon nor white precipitate after pretreatment, thereby improving the pretreatment efficiency while ensuring the accuracy of the measurement result.
[0019] More preferably, in step (3), the volume ratio of dichloromethane to N-methylpyrrolidone in the mixed solvent is 8:2.
[0020] Among them, the preferred mixed solvent of the present invention is a mixture of dichloromethane and N-methylpyrrolidone, wherein dichloromethane has good solubility and is cheaper than acetone; N-methylpyrrolidone can be completely mixed with most organic solvents and can be used to dissolve polymer materials and adhesives. Under the preferred mixed volume ratio of the present invention, the two have better dissolution efficiency and lower cost.
[0021] Preferably, in step (3), the temperature of the ultrasonic treatment is room temperature-35°C, the frequency is 40 Hz, and the time is 10 min.
[0022] Preferably, in step (3), the mixed solvent poured out after the third and / or fourth ultrasound is used as the mixed solvent added in the first and / or second ultrasound for pretreatment in the next test.
[0023] Preferably, in step (4), the drying temperature is 120°C ± 2°C, and the drying time is 60 minutes until constant weight is reached.
[0024] Preferably, resin content = [1-(M2-M0) / (M1-M0)] × 100%; fiber surface density = (M2-M0) / A;
[0025] Wherein, M0: the weight of the container in step (1), in g;
[0026] M1: the total weight of the container and the prepreg sample to be tested in step (2), in g;
[0027] M2: the total weight of the container and the fiber in step (4), in g;
[0028] The unit of A is m 2 ; The unit of resin content is %; the unit of fiber surface density is g / m 2 .
[0029] Preferably, when weighing, M0, M1, and M2 are accurate to 0.0001 g.
[0030] The technical solution of the present invention achieves the following beneficial technical effects:
[0031] The invention uses a mixed solvent of dichloromethane and N-methylpyrrolidone as a cleaning solvent during ultrasound, and specifically defines the mixed volume ratio of the two, the ratio of the mixed solvent volume to the mass of the sample to be tested, the temperature, frequency, time and other conditions of each ultrasonic treatment. Only four ultrasonic cleaning treatments are performed to achieve effective decomposition of resin and fiber in epoxy prepreg or polyester prepreg treatment. After cleaning, the bonding phenomenon in the fiber is reduced, no white precipitate is observed, the fiber loss is reduced, the stability and accuracy of determining the resin content and the fiber surface density content are higher, and the invention is suitable for the treatment of epoxy prepreg or polyester prepreg with a resin content of 33-50%.
[0032] The present invention utilizes a mixed solvent to improve the solubility of the resin matrix, and the resin can be cleaned only by repeating the ultrasonic cleaning step 4 times. Compared with the existing method, the number of cleaning times and the amount of solvent used are significantly reduced, and the work efficiency is significantly improved. Among them, after a single test is repeated 3 times, the total amount of solvent used can be reduced by 43% (from 2100mL to 1200mL), and the work efficiency can also be improved by 43% (from 7 ultrasonic cleaning times to 4 times).
[0033] The present invention uses a mixed solvent to improve the cleaning efficiency while reducing the amount of solvent used, saving processing costs and achieving the effect of reducing costs and increasing efficiency. Moreover, the 3rd to 4th cleaning mixed reagent can be used for the 1st to 2nd cleaning of other samples after filtering, which can improve the reuse rate of the reagent and further save costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The actual picture of the comparative example 1 of the present invention after ultrasonic cleaning for 4 times;
[0035] The solvent is pure dichloromethane; the left picture shows the fiber after ultrasonic cleaning and drying, the right picture shows the fiber after ultrasonic cleaning, Figure 2-9 same;
[0036] Figure 2 The actual picture of Example 1 of the present invention after ultrasonic cleaning for 4 times;
[0037] The solvent is a mixed solvent of dichloromethane + NMP, and the mixing ratio is 8:2;
[0038] Figure 3 The actual picture of Example 2 of the present invention after ultrasonic cleaning for 4 times;
[0039] The solvent is a mixed solvent of dichloromethane + NMP, and the mixing ratio is 6:4;
[0040] Figure 4 The actual picture of Example 3 of the present invention after ultrasonic cleaning for 4 times;
[0041] The solvent is a mixed solvent of dichloromethane + NMP, and the mixing ratio is 5:5;
[0042] Figure 5 The actual picture of Example 4 of the present invention after ultrasonic cleaning for 4 times;
[0043] The solvent is a mixed solvent of dichloromethane + NMP, and the mixing ratio is 4:6;
[0044] Figure 6 The actual picture of Example 5 of the present invention after ultrasonic cleaning for 4 times;
[0045] The solvent is a mixed solvent of dichloromethane + NMP, and the mixing ratio is 2:8;
[0046] Figure 7 The actual picture of the comparative example 2 of the present invention after ultrasonic cleaning 7 times;
[0047] Wherein, the solvent is pure acetone;
[0048] Figure 8 The actual picture of comparative example 4 of the present invention after ultrasonic cleaning 7 times;
[0049] The solvent is a mixed solvent of acetone + ethanol, and the mixing ratio is 8:2;
[0050] Fig. 9 The actual picture of comparative example 5 of the present invention after ultrasonic cleaning 7 times;
[0051] The solvent is a mixed solvent of acetone + dichloromethane, and the mixing ratio is 8:2;
[0052] Fig.10 Flow chart of the process design of the assay method of the present invention. DETAILED DESCRIPTION
[0053] The raw materials used in the following embodiments and comparative examples of the present invention are:
[0054] Prepreg to be tested: provided by China Aviation Manufacturing Technology Research Institute; brand: AC328 / CF8652 / 40; the prepreg to be tested meets the following technical indicators: Prepreg surface weight: 488±18g / m 2 ; Fiber surface weight: 293±8g / m 2 ; Resin content: 40±2%; Volatile content ≤0.8%; Viscosity: Level 1 or 2.
[0055] Example 1
[0056] like Fig.10 As shown, this embodiment provides a method for determining the resin content and fiber surface density content of a prepreg, comprising the following steps:
[0057] (1) Cool the 500 mL beaker that has been dried at 120 °C for 60 min to room temperature and weigh it to the nearest 0.0001 g, recorded as M0;
[0058] (2) A sample ≥50 mm from the edge is selected as the prepreg sample to be tested, and the sample does not contain burrs. The size of the prepreg sample to be tested is 100 mm × 100 mm (i.e., the area of the prepreg sample to be tested);
[0059] Cut the prepreg sample to be tested into 10 mm × 100 mm pieces, place them in the beaker in step (1), weigh them accurately to 0.0001 g, and record the total weight of the beaker and the prepreg sample to be tested as M1;
[0060] (3) Add 100 mL of the mixed solvent to the beaker of step (2), ultrasonicate for 10 min at 35° C. and 40 Hz, and pour out the mixed solvent; wherein the volume ratio of dichloromethane to N-methylpyrrolidone (NMP) in the mixed solvent is 8:2, see No. 2 in Table 1 for details;
[0061] Continue to add new 100 mL of mixed solvent into the beaker, and repeat the ultrasonic treatment 4 times; after the treatment, the remaining fibers in the beaker are obtained after the treatment;
[0062] The mixed solvent poured out after the third and / or fourth ultrasonic treatment can be used as the mixed solvent added during the first and / or second ultrasonic treatment in the next pretreatment.
[0063] (4) Dry the fiber together with the beaker at 120°C for 60 min until constant weight is reached. After drying, cool to room temperature and weigh the total weight of the container and the fiber to an accuracy of 0.0001 g, and record it as M2.
[0064] Each group of prepreg samples to be tested was tested three times, and the results were averaged; a total of 1200 mL of mixed solvent was consumed in the three experiments.
[0065] (5) Calculate the resin content and fiber surface density of the prepreg to be tested respectively.
[0066] Example 2
[0067] This embodiment provides a method for determining the resin content and fiber surface density content of a prepreg. The difference from Embodiment 1 is that the solvent used in step (3) is different. The volume ratio of dichloromethane and N-methylpyrrolidone (NMP) in the mixed solvent used in this embodiment is 6:4, see sequence number 3 in Table 1 for details; other parameters and steps are the same as those in Embodiment 1.
[0068] Each group of prepreg samples to be tested was tested three times, and the results were averaged; a total of 1200 mL of mixed solvent was consumed in the three experiments.
[0069] Example 3
[0070] This embodiment provides a method for determining the resin content and fiber surface density content of a prepreg. The difference from Embodiment 1 is that the solvent used in step (3) is different. The volume ratio of dichloromethane and N-methylpyrrolidone (NMP) in the mixed solvent used in this embodiment is 5:5, see sequence number 4 in Table 1 for details; other parameters and steps are the same as those in Embodiment 1.
[0071] Each group of prepreg samples to be tested was tested three times, and the results were averaged; a total of 1200 mL of mixed solvent was consumed in the three experiments.
[0072] Example 4
[0073] This embodiment provides a method for determining the resin content and fiber surface density content of a prepreg. The difference from Embodiment 1 is that the solvent used in step (3) is different. The volume ratio of dichloromethane and N-methylpyrrolidone (NMP) in the mixed solvent used in this embodiment is 4:6, see sequence number 5 in Table 1 for details; other parameters and steps are the same as those in Embodiment 1.
[0074] Each group of prepreg samples to be tested was tested three times, and the results were averaged; a total of 1200 mL of mixed solvent was consumed in the three experiments.
[0075] Example 5
[0076] This embodiment provides a method for determining the resin content and fiber surface density content of a prepreg. The difference from Embodiment 1 is that the solvent used in step (3) is different. The volume ratio of dichloromethane and N-methylpyrrolidone (NMP) in the mixed solvent used in this embodiment is 2:8, see sequence number 6 in Table 1 for details; other parameters and steps are the same as those in Embodiment 1.
[0077] Each group of prepreg samples to be tested was tested three times, and the results were averaged; a total of 1200 mL of mixed solvent was consumed in the three experiments.
[0078] Comparative Example 1
[0079] This comparative example provides a method for determining the resin content and fiber surface density content of a prepreg. The difference from Example 1 is that the solvent used in step (3) is different. In this comparative example, the mixed solvent is replaced by pure dichloromethane. For details, see No. 1 in Table 1. The other parameters and steps are the same as those in Example 1.
[0080] Each group of prepreg samples to be tested was tested three times, and the results were averaged; a total of 1200 mL of mixed solvent was consumed in the three experiments.
[0081] Comparative Example 2
[0082] This comparative example provides a method for determining the resin content and fiber surface density of a prepreg. The difference from Example 1 is that the solvent used in step (3) is different. In this comparative example, the mixed solvent is replaced with pure acetone, and the ultrasonic treatment is repeated 7 times (i.e., 100 mL of acetone is consumed each time), and each ultrasonic treatment is stirred for 5 minutes before the next ultrasonic treatment; see No. 7 in Table 1 for details; other parameters and steps are the same as those in Example 1.
[0083] Each group of prepreg samples to be tested was tested three times, and the results were averaged; a total of 2100 mL of acetone was consumed in the three experiments.
[0084] Comparative Example 3
[0085] This comparative example provides a method for determining the resin content and fiber surface density content of a prepreg. The difference from Example 1 is that the solvent used in step (3) is different. In this comparative example, the mixed solvent is replaced by a mixed solvent of acetone and NMP in a volume ratio of 8:2, see sequence number 8 in Table 1 for details; the other parameters and steps are the same as those in Example 1.
[0086] Each group of prepreg samples to be tested was tested three times, and the results were averaged; a total of 1200 mL of mixed solvent was consumed in the three experiments.
[0087] Comparative Example 4
[0088] This comparative example provides a method for determining the resin content and fiber surface density content of a prepreg. The difference from Example 1 is that the solvent used in step (3) is different. In this comparative example, the mixed solvent is replaced with a mixed solvent of acetone and ethanol in a volume ratio of 8:2, and the ultrasonic treatment is repeated 7 times; and after each ultrasonic treatment, stirring treatment is required for 5 minutes before the next ultrasonic treatment; see sequence number 9 in Table 1 for details; other parameters and steps are the same as those in Example 1.
[0089] Each group of prepreg samples to be tested was tested three times, and the results were averaged; a total of 2100 mL of mixed solvent was consumed in the three experiments.
[0090] Comparative Example 5
[0091] This comparative example provides a method for determining the resin content and fiber surface density content of a prepreg. The difference from Example 1 is that the solvent used in step (3) is different. In this comparative example, the mixed solvent is replaced with a mixed solvent of acetone and dichloromethane in a volume ratio of 8:2, and the ultrasonic treatment is repeated 7 times; and after each ultrasonic treatment, stirring treatment is required for 5 minutes before the next ultrasonic treatment; see sequence number 10 in Table 1 for details; other parameters and steps are the same as those in Example 1.
[0092] Each group of prepreg samples to be tested was tested three times, and the results were averaged; a total of 2100 mL of mixed solvent was consumed in the three experiments.
[0093] Result analysis: The actual pictures of the prepreg to be tested in the embodiment and comparative example after ultrasonic cleaning and drying are as follows Figure 1-9 The experimental parameters, experimental data, resin content and fiber surface density analysis results of each embodiment and comparative example are shown in Tables 1-3.
[0094] Table 1
[0095]
[0096] Table 2
[0097]
[0098] Wherein, resin content = (1-fiber mass / test sample mass) × 100%; fiber surface density = fiber mass / sample area; technical indicators: fiber surface density: 293 ± 8g / m 2 ; Resin content: 40±2%; Technical indicators refer to the specific quantitative standards used to measure and evaluate the experimental effects and characteristics of the experimental objects during the experiment; Among them, the average value retains three significant figures, and the standard deviation and dispersion coefficient retain two significant figures.
[0099] Table 3
[0100]
[0101] According to Table 1, Table 2, and Table 3, after ultrasonic cleaning of Comparative Examples 1, 2, 4, and 5, white precipitates appeared in the fibers, or there was a more serious bonding phenomenon, the decomposition effect of the resin and the fiber was not good, and it was easy to cause misjudgment, resulting in the need for re-cleaning of the sample. And after the treatment of Comparative Examples 1, 4, and 5, the measured numerical content and fiber surface density did not meet the relative standard deviation requirements of the reference standard, and the accuracy of the test was not high. At the same time, acetone is a precursor chemical with a low storage capacity, and is relatively strict in procurement and waste liquid recovery, and the cost is relatively high compared to dichloromethane, so it is not used in industrial applications.
[0102] The decomposition effect of the resin and fiber in Examples 1-5 and Comparative Example 3 is better, and the number of ultrasonic cleaning and separation experiments is less, and the total amount of solvent used is less, which is based on the stronger dissolving ability of NMP. Further comparing the relative standard deviation of the numerical content and fiber surface density of each experimental group, when a mixed solvent of dichloromethane + NMP (8:2) is selected, the accuracy of the test is higher. At the same time, in the experimental group where the mixed solvent is dichloromethane + NMP (8:2), 3 repeated tests also have good stability. And when the mixing ratio of dichloromethane + NMP is 8:2, the cost is lower.
[0103] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the claims of this patent application.
Claims
1. A method for determining the resin content and fiber surface density of a prepreg, characterized in that: The following steps are involved: (1) Cooling the dried container to room temperature and weighing the container; (2) cutting the prepreg sample to be tested, placing it into the container of step (1), and weighing the total weight of the container and the prepreg sample to be tested; (3) adding a mixed solvent to the container of step (2), pouring out the mixed solvent after the first ultrasonic treatment; adding a new mixed solvent, pouring out the mixed solvent after the second ultrasonic treatment, and then adding a new mixed solvent, repeating the ultrasonic treatment for a total of 4 times; after the ultrasonic treatment, the fiber remaining in the container is the treated fiber; the mixed solvent is dichloromethane and N-methylpyrrolidone; (4) drying the fiber together with the container, cooling to room temperature after drying, and weighing the total weight of the container and the fiber; (5) Calculate the resin content and fiber surface density of the prepreg sample to be tested respectively.
2. The measuring method according to claim 1, characterized in that In step (1), the drying temperature is 120°C ± 2°C and the drying time is 60 min; In step (2), the prepreg sample to be tested is epoxy prepreg or polyester prepreg; and the resin mass content of the prepreg sample to be tested is 33-50%.
3. The measuring method according to claim 1, characterized in that In step (2), a sample ≥50 mm away from the edge is selected as the prepreg sample to be tested, the area of the prepreg sample to be tested is recorded as A, and the size of the selected prepreg sample to be tested is (100±1) mm×(100±1) mm; after shearing, the size of the prepreg sample to be tested is ≤10 mm×100 mm.
4. The measuring method according to claim 1, characterized in that In step (3), the ratio of the mass of the prepreg sample to be tested to the volume of the mixed solvent added once is (4-6) g:100 mL.
5. The measuring method according to claim 1, characterized in that In step (3), the volume ratio of dichloromethane and N-methylpyrrolidone in the mixed solvent is (8-2): (2-8).
6. The assay method according to claim 5, wherein In step (3), the volume ratio of dichloromethane to N-methylpyrrolidone in the mixed solvent is 8:
2.
7. The measuring method according to claim 1, characterized in that In step (3), the temperature of ultrasonic treatment is room temperature-35°C, the frequency is 40 Hz, and the time is 10 min.
8. The assay method according to claim 1, wherein In step (3), the mixed solvent poured out after the third and / or fourth ultrasound treatment is used as the mixed solvent added in the first and / or second ultrasound treatment for pretreatment in the next test.
9. The measuring method according to claim 1, characterized in that In step (4), the drying temperature is 120°C ± 2°C and the drying time is 60 minutes.
10. The assay method according to any one of claims 1 to 9, characterized in that: The calculation method of resin content and fiber surface density is: resin content = [1-(M2-M0) / (M1-M0)] × 100%; fiber surface density = (M2-M0) / A; Wherein, M0: the weight of the container in step (1), in g; M1: the total weight of the container and the prepreg sample to be tested in step (2), in g; M2: the total weight of the container and the fiber in step (4), in g; When weighing, M0, M1, and M2 are accurate to 0.0001g; the unit of A is m 2 ; The unit of resin content is %; the unit of fiber surface density is g / m 2 .
Citation Information
Cited By
Method and device for testing resin content and fiber surface density of thermoplastic prepreg
CN121830379A
Method and apparatus for testing resin content and fiber areal density of thermoplastic prepreg
CN121830379B